Analysis of grasping strategies using sensor based systems - Luai, Jonathan Wei Jie (2018)
Analysis of Grasping Strategies for Stroke Patients in Rehabilitative Technologies for Final Year Project Academic Year 17/18 explores the novel approach of using inexpensive electronic materials to develop a methodology for analysing the grasping strategies of individual subjects. The data for these grasping strategies can then be extrapolated and extended to hemiparetic stroke patients who are undergoing stroke rehabilitative treatment. In doing so, the aim is to build a reliable algorithm in predicting the grasp pattern of individuals when they participate in upper limb rehabilitation. The use of these data would also serve as a good source of reference in the future development of the project, which could potentially involve the system integration of a portable lightweight interactive board, as well as a gaming platform for stroke patients. This paper hence presents the experimental and design process on the various methods used for the grasping analysis and data collection.